Legal Protection in Medical Disputes for Doctors in Relation to The Principle of Lex Specialist - Zamrotul Damayanti, Lukluk; Tohir Suriaatmadja, Toto; Lucyati, Alma (Yayasan Studi Cendekia Indonesia (YSCI), 2023)
Health is one of the constitutional rights protected by law. The importance of health in everyday life makes many people hope to get a cure when they see a doctor. Patient expectations that differ from the results obtained sometimes lead to medical disputes. Conflicts that occur between doctors and patients if they cannot be resolved by mediation usually the patient or the patient's family will report to the authorities. Some law enforcers, in this case the police, still use the Criminal Code or Civil Code as the basis for charges without looking at other more specialised laws such as the Medical Practices Act (UUPK). The purpose of this thesis is to find out the procedures for legal protection for doctors in medical disputes and also to find out the application of the Lex Specialist principle of Article 79 letter (C) of the GCPL in relation to the lex generalis principle of the Civil Code in resolving medical disputes for doctors. This research uses a normative juridical approach and is analytically descriptive. From the results of this study, it can be concluded by the author that doctors will get legal protection in medical disputes if they have fulfilled administrative obligations, namely having STR and SIP as a condition for practicing medicine and performing actions according to SOPs, Professional Standards and conducting inform consent completely and clearly and filling out medical records in accordance with the actions performed.